THE INFLUENCE OF PICTURE STORY BOOKS ON THE ABILITY TO READ NARRATIVE TEXTS OF CLASS VII STUDENTS OF SMP NEGERI 1 BONTONOMPO, GOWA REGENCY - mattayang, alif nurqalbi; -, Sakaria; Nojeng, Asis (Bahasa Indonesia Prima, 2025)
This study aims to (1) describe the narrative text reading ability of seventh-grade students at SMP Negeri 1 Bontonompo before using picture storybooks; (2) describe the narrative text reading ability of seventh-grade students at SMP Negeri 1 Bontonompo after using picture storybooks; (3) prove that there is a significant effect of using picture storybooks on the narrative text reading ability of seventh grade students at SMP Negeri 1 Bontonompo. This research is quantitative in nature, using an experimental method with a pre-test and post-test single group design. The data collection method used pre-tests and post-tests. The data analysis method used descriptive and inferential analysis. The results showed that before using picture storybooks, the narrative text reading ability of seventh-grade students at SMP Negeri 1 Bontonompo was low or poor, with an average pre-test score of 57. After using picture storybooks, the narrative text reading ability of seventh-grade students at SMP Negeri 1 Bontonompo increased significantly, with an average post-test score of 76. There was a significant effect of using picture storybooks on the narrative text reading ability of seventh-grade students at SMP Negeri 1 Bontonompo with a value of 0.000 < 0.05, indicating that picture storybooks had an effect on students’ narrative text reading ability.